2003
DOI: 10.1002/chin.200350243
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite Synthesized by Alkaline Hydrothermal Treatment of Bottom Ash from Combustion of Municipal Solid Wastes.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The mineral can form under hydrothermal conditions (Fukui et al, 2009) due to the alkalis supplied by the BA (1.8 wt.% NaO, 1.2 wt.% K 2 O). The formation of zeolites during HT, in presence of MSWI BA has been reported in other studies (Deng et al, 2016;Penilla et al, 2003;Temuujin et al, 2002). It is however unusual that no Ca 2+ could be detected, since K-Phillipsite readily incorporates this element.…”
Section: Influence Of Autoclaving On Phase Composition and Microstruc...supporting
confidence: 70%
“…The mineral can form under hydrothermal conditions (Fukui et al, 2009) due to the alkalis supplied by the BA (1.8 wt.% NaO, 1.2 wt.% K 2 O). The formation of zeolites during HT, in presence of MSWI BA has been reported in other studies (Deng et al, 2016;Penilla et al, 2003;Temuujin et al, 2002). It is however unusual that no Ca 2+ could be detected, since K-Phillipsite readily incorporates this element.…”
Section: Influence Of Autoclaving On Phase Composition and Microstruc...supporting
confidence: 70%
“…As waste disposal by incineration increases, there is need to develop innovative applications of IBA with environmental and economic benefits.. Currently, IBA is utilized as filler for road base construction (Santagata, et al, 2014), raw material for cement production (Li, et al, 2012), cement or aggregates substitute for concrete production (Kuo, et al, 2013), material for zeolites (Penilla, et al, 2003) and tobermorite synthesis (Jing, et al, 2007), and adsorbent for heavy metal removal (Zhang, et al, 2011). These approaches generally require complex and/or costly pre-treatments before it can be used for usually low value added applications.…”
Section: Introductionmentioning
confidence: 99%
“…The minority crystalline phases were ␣-Fe 2 O 3 (hematite) and probably, Mg 2 C 3 . Samples with potential adsorption or cation exchange properties, obtained previously from the transformation of the bottom ash after various treatments [19], were characterized by X-ray diffractometry (XRD), scanning electron microscopy (SEM) and energy-dispersive X-ray analysis. The surface areas and pore size distribution were measured by a multipoint BrunauerEmmett-Teller (BET) method.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work [19], we studied the transformation of bottom ash as a function of various types of HT in NaOH and water, at temperatures ranging from ambient to 200 • C. The results showed that bottom ash was transformed in compounds with potential immobilization capacity, such as zeolite-type A (Na 6 The present paper focuses on the retention of Cs + , Cd 2+ , Pb 2+ and Cr 3+ by the aforementioned compounds previously synthesized by Peña et al [19], which would represent a new application of bottom ash in environmental waste disposal. The changes in the micro porosity, specific surface (BET-N 2 ) and microstructure of the bottom ash are also discussed.…”
Section: Introductionmentioning
confidence: 98%